Kondisi Jepang Pasca Gempa Bumi dan Tsunami dalam Ehon Kataritsugi Ohanashi Ehon 3-gatsu 11-nichi - Damayanti, Silvia; Wedayanti, Ni Putu Luhur; Wangsa, I Gusti Ngurah Jun Arya (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 6 No 2 (2024), 2024)
This research is titled "Post-Earthquake and Tsunami Conditions in Japan in Ehon ". This research aims to understand the post-earthquake and tsunami conditions in Japan following the Tohoku earthquake and tsunami in 2011, as depicted in the ehon series "Kataritsugi Ohanashi Ehon 3-gatsu 11-nichi". Data collection was conducted using library research methods, observation techniques, and note-taking. The data analysis technique used was descriptive analysis, and the presentation of data analysis used both formal and informal methods. The theories employed were the Sociology of Literature Theory and Charles Sanders Peirce's Semiotics Theory. The results obtained in this research indicate that the natural disaster events of the Tohoku earthquake and tsunami in 2011 in Japan are reflected in the collection of ehon "Kataritsugi Ohanashi Ehon 3-gatsu 11-nichi". Within the ehon collection, the earthquake and tsunami are depicted as causing significant losses, both in terms of loss of life and economic impact on Japan. Interestingly, the effects of the earthquake and tsunami narrated in the ehon are presented in a way that is not frightening and easily understandable by children, serving as an educational resource about earthquakes and tsunamis.